RANCANG BANGUN SISTEM INFORMASI AKADEMIK LEMBAGA KURSUS BERBASIS WEB PADA OHAYO DRAWING SCHOOL BATAM - Sulestra, Ikhwan; Tukino, Tukino (LPPM Universitas Putera Batam, 2021)
Technology and information are the most effective solutions to solve various problems, especially in organizations both small and large. The presence of technology is not to replace human work but can help and facilitate all work that occurs in an organization. The academic information system of the course institution that was built can help the course institution in better data management and delivery of information through the official website and simplify the registration process, attendance, report making and others. The data collection method used is by using observation, literature study, and interviews. the system design method used is the waterfall where the stages are planning, analysis, designing, and testing the system. Website design uses CodeIgniter 4, Bootstrap 4, and MySQL framework to shorten the time with satisfactory results. With the development of this information system is expected to be a solution to the problems faced by the Ohayo Drawing School course institution in conveying information, managing data, and other features.